Dakwah Tentang Kepemimpinan: Narasi Dakwah Media Online KeIslaman: (Studi Rumaysho.com dan Kompretif Islami.co) - Cholida Fahrun; Alfan Bachtiar (Brand Communication, 2022)
This paper analyzes the emergence of the comparative Islamic da'wah study movement on social media islami.co and rumaysho.com, especially in social institutions that massively carry out popular da'wah programs among Muslims. Contemporary da'wah movements from time to time continue to change and the da'wah programs of non-Muslim leaders. This study is important to do to see how the contemporary da'wah movement strengthens its authority in society. Specifically, this article will address the following questions. How is Rumaysho.com's da'wah narrative about non-Muslim leaders? How is Islam.co's da'wah narrative about non-Muslim leaders. This study was conducted through field studies and supported by relevant literature. The results of the study indicate that the contestation carried out by Narrative Da'wah against the old religious authorities was carried out through efforts to create a space for popular piety and hijrah for the community. Then the Da'wah Narrative is not politically contested, but about da'wah.